"It was only harmless banter!" The development and preliminary validation of the moral disengagement in sexual harassment scale. Issue 3 (9th September 2015) - Page, Thomas E.; Pina, Afroditi; Giner‐Sorolla, Roger
Abstract : Sexual harassment represents aggressive behavior that is often enacted instrumentally, in response to a threatened sense of masculinity and male identity. To date, however, theoretical attention to the social cognitive processes that regulate workplace harassment is scant. This article presents the development and preliminary validation of the Moral Disengagement in Sexual Harassment Scale (MDiSH); a self‐report measure of moral disengagement in the context of hostile work environment harassment. Three studies (total n  = 797) document the excellent psychometric properties of this new scale. Male U.K. university students (Study 1: n  = 322) and U.S. working males (Studies 2 and 3: n  = 475) completed the MDiSH and an array of measures for construct validation. The MDiSH exhibited positive correlations with sexual harassment myth acceptance, male gender identification, and hostile sexism. In Study 3, participants were exposed to a fictitious case of hostile work environment harassment. The MDiSH attenuated moral judgment, negative emotions (guilt, shame, and anger), sympathy, and endorsement of prosocial behavioral intentions (support for restitution) associated with the harassment case. Conversely, the MDiSH increased positive affect (happiness) about the harassment and attribution of blame to the female complainant. Implications for practice and future research avenues are discussed. Aggr. Behav. 42:254–273, 2016. © 2015 Wiley Periodicals, Inc.